(untitled) (Castilla. Estudios de Literatura, 2026)
This article examines the process of posthumous canonization of Miguel Delibes and its role in the construction of Castilian identity during the period 2010–2013. Drawing on paratextual theory and the polysystem approach, the study analyses journalistic, academic, and institutional discourses produced in Castile and León following the author’s death. Particular attention is paid to the tension between universalist interpretations of Delibes’s work and its regional instrumentalization as a cultural symbol. The article argues that literary canon formation is closely intertwined with cultural policy, collective memory, and identity-building processes within a specific territorial context.